Ant colony optimization algorithms for digital device diagnostics - Speranskii, D. V. (Automatic control and computer sciences, 2015)
This paper investigates the possibility of solving two problems of digital device diagnostics by means of ant colony optimization. It is shown how these problems can be reduced to the classical traveling salesman and set covering problems which are efficiently solved by ant colony optimization algorithms.